A escala ótima de operação das escolas. - Cordova, Rogerio de Andrade (1982)
This study analyses the costs in a sample of schools in the state of Rio de Janeiro and Federal District (Bra silia) . The main purpose is to determine their optimal scale and to analyse the efficiency in the utilization of their h~man and. infraestructural resources. The analysis demonstrates that the optimal scale is estimated by the minimum point in the long run average costs curves, determining the ideal size the schools should reach . in order to obtain the maximutn of effidien'cy -and efficacy. This efficiency is observed in terms of the intensity of utilized physical facilities and the adeguate allocation of human resources, according to the type 9f we are dealing with and the number of students enrolled. schools We intend to demonstrate that the educational planning system can be able to improve its efficiency through the approach of micro. econornics theory , .. mo-reover. focusing the guestioris related to the production and costs functions. Finally, the adeguate utilization of these concepts can be very important to detect and understand the proposed and debated dicotomy between guantity and guality in Brazil. A specific system of planning that consider theses aspects of the eco~omical theory is able to improve the eguality within the educational system for large groups of children and young people. In summary, what we meant is that guantity, rather than an obstacle, can support a higher quality éducátional system, since there are scientific and technical competence complemented by political decision making.